2022
DOI: 10.5005/jp-journals-10071-24387
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Awareness Level Regarding Organ Donation among Healthcare Professionals and Students in India

Abstract: Introduction Organ donation can be a life-saving opportunity for patients with severe organ failure. In India, the rate of organ donation of the deceased Indian population is exceptionally low. This necessitates enhancing awareness regarding organ donation among health care professionals and students, which can motivate the general population. Aim To assess and analyze the awareness level of healthcare professionals and students on organ donation in order to suggest pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In addition, Rios et al conducted a cross-sectional study in Spanish and concluded that there is a lack of knowledge among the medical students [23]. Chandrasekaran et al's study, which also highlights the knowledge gap and improvement needs among Indian healthcare providers, supports the findings of our study as well [24]. All previous studies have shown that there is a great demand for education among healthcare providers.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, Rios et al conducted a cross-sectional study in Spanish and concluded that there is a lack of knowledge among the medical students [23]. Chandrasekaran et al's study, which also highlights the knowledge gap and improvement needs among Indian healthcare providers, supports the findings of our study as well [24]. All previous studies have shown that there is a great demand for education among healthcare providers.…”
Section: Discussionsupporting
confidence: 87%
“…The immediate post-trauma stage, particularly in the context of brainstem death is extremely important in maintaining the viability of organs as well as providing resources and information to the family in helping them make decisions about organ donation 22. It should be noted that most of the population in India do not have a preference regarding organ donation and general awareness is lacking 23–26. It is, therefore, a very daunting task for a healthcare provider to counsel the family about organ donation, particularly when the healthcare provider is not well versed in the process or management—which is the case for most doctors working in rural regions of the country.…”
Section: Global Health Problem Analysismentioning
confidence: 99%